Effectiveness of traditional healers in treating mental disorders - a systematic review (2016)
Traditional healers form a major part of the mental health workforce worldwide. Despite this, little systematic examination has been done of their effectiveness in treating mental illness or alleviating psychological distress. In this Review, we aim to fill this gap, with a focus on quantitative outcomes. We searched four databases and reference lists for papers that explicitly measured the effectiveness of traditional healers on mental illness and psychological distress. Eligible papers were assessed for quality, and outcomes and other details were extracted with the use of a standardized template. 32 eligible papers from 20 countries were included. The published literature on this topic is heterogeneous and studies are generally of poor quality, although some findings emerge more consistently. Some evidence suggests that traditional healers can provide an effective psychosocial intervention. Their interventions might help to relieve distress and improve mild symptoms in common mental disorders such as depression and anxiety. However, little evidence exists to suggest that they change the course of severe mental illnesses such as bipolar and psychotic disorders. Nevertheless, qualitative changes that are captured poorly by conventional rating scales might be as important as the quantitative changes reviewed here. We conclude by outlining the challenges involved in assessing the effectiveness of traditional healers.